Assessment of heavy metals in selected meat products / Noor Hidayah Halim - Halim, Noor Hidayah (Faculty of Applied Sciences, 2016)
Contamination of heavy metals in food may be due to natural sources or anthropogenic source. Human could directly or indirectly consume heavy metals via food chain. A total of 12 samples of meat products consisting of meatball, minced beef, sausages and burger patties were randomly purchased and analyzed for heavy metals concentration using Atomic Absorption Spectroscopy. This study aimed to investigate the presence of essential metals such as Cu, Zn and toxic metals such as Cd, Pb in selected meat products and to compare the concentration of Cu, Zn, Cd and Pb with the limit guidelines set by the Malaysia Food Regulation 1985. The concentration of the Zn obtained from the 12 meat products was in order of meatball > sausages = burger patties> minced beef. However, the order of the level of the Cu obtained was different, minced beef > meatball > sausages > burger patties. For Pb and Cd, the concentrations were below the detection limit. The heavy metals concentrations were less than the guidelines limit set by the Malaysia Food Regulation 1985.